A proposed interpretation of the phrase "subject to tax" in section 23M(2)(i)(aa) of the Income Tax Act, No 58 of 1962, when read in context of South African Tax Treaties - Leshomo, Otladisa Patrick (Department of Commercial Law, 2022)
Following the tax policy recommendation of the Organisation for Economic Co-operation and Development (‘OECD')/Group of Twenty (‘G20') member countries, under the OECD/G20 Base Erosion and Profit Shifting Project: Action 4 (‘BEPS Action 4'), the South African legislature recently enacted an internationally focused anti-avoidance provision, in section 23M of the Income Tax Act No.58 of 1962 (‘the Act'). The provision aims to limit interest expenditure incurred by the debtor, provided that the corresponding interest income accrued to non-resident creditor is, among other things, (which is most important,) not ‘subject to tax' in terms of section 23M(2)(i)(aa) of the Act. However, despite its importance, the phrase ‘subject to tax' is not defined in section 23M or in the general definition of the Act nor has the matter came before the South African courts for consideration. This has lead to confusion among taxpayers, and fragmented views among South African tax scholars, tax practitioners and the South African Revenue Services (‘SARS'). On the other hand, the phrase ‘subject to tax' has a long history in international tax law and it appears inter alia, in the South Africa-France, South Africa-Sweden and South Africa-Germany interest distributive rules tax treaties. The objective of this study is, based on the canons of interpretation of fiscal legislation, to propose an interpretation of phrase ‘subject to tax,' particularly when read in context of South African tax treaties, and thereafter apply it in the context of foreign corporate tax, normal tax and withholding tax on interest. The author concludes that the phrase ‘subject to tax' means that non-resident creditors must ‘actually' be liable to pay tax on interest, subject to deductions, set-offs and foreign tax reliefs. It is the authors view that if foreign corporate tax falls within the ambit of the word ‘tax' as defined in the applicable tax treaty and/or ‘covered tax' therein, the word ‘tax' encompass foreign corporate tax ‘actually' imposed on a non-resident creditor in its country, as a result of accrued interest from the South African source.